2020
DOI: 10.1002/agg2.20018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and potassium fertilization in no‐till hard red spring wheat production

Abstract: There is a need to develop more efficient nutrient management strategies to maximize wheat (Triticum aestivum L.) grain yields and increase grain protein levels. Urea, most widely used N fertilizer, is susceptible to substantial losses, resulting in low nitrogen use efficiency (NUE). This study assessed the effect of N and K fertilization on hard red spring wheat production under dryland no-till conditions in Montana. A field experiment was conducted during one growing season at two locations in Northcentral M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
2
1
0
Order By: Relevance
“…In this study, across all site‐years, grain protein content increased with N rate. This agrees with findings by Walsh (2020), who reported that wheat grain protein content may be enhanced with N application even if grain yield is not increased. Several authors have also found a positive relationship between N rate and grain protein (Fiez et al., 1994; Kindred et al., 2008; Terman et al., 1969; Vaughan et al., 1990).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, across all site‐years, grain protein content increased with N rate. This agrees with findings by Walsh (2020), who reported that wheat grain protein content may be enhanced with N application even if grain yield is not increased. Several authors have also found a positive relationship between N rate and grain protein (Fiez et al., 1994; Kindred et al., 2008; Terman et al., 1969; Vaughan et al., 1990).…”
Section: Resultssupporting
confidence: 93%
“…In general, across all site-years, NUE was lower at very high N rates of 252 and 336 kg N ha −1 . This is typical of NUE trends as observed by several authors (Dobermann, 2005;Walsh & Walsh, 2020). The reason for the decrease in NUE with increased N rates is associated with increased loss due to denitrification and leaching.…”
Section: Grain N Uptake and N Use Efficiencysupporting
confidence: 81%
See 1 more Smart Citation